The Emerging Neuroscience of Intrinsic Motivation: A New Frontier in Self-Determination Research - Di Domenico, Stefano I.; Ryan, Richard M. (Frontiers in Human Neuroscience, 2017)
Intrinsic motivation refers to people’s spontaneous tendencies to be curious and interested, to seek out challenges, and to exercise and develop their skills and knowledge, even in the absence of operationally separable rewards. Over the past four decades, experimental and field research guided by self-determination theory (Ryan & Deci, 2017) has found intrinsic motivation to predict enhanced learning, performance, creativity, optimal development, and psychological wellness. Only recently, however, have studies begun to examine the neurobiological substrates of intrinsic motivation. In the present paper, we trace the history of intrinsic motivation research, compare and contrast intrinsic motivation to closely related topics (flow, curiosity, trait plasticity), link intrinsic motivation to key findings in the comparative affective neurosciences, and review burgeoning neuroscience research on intrinsic motivation. We review converging evidence suggesting that intrinsically motivated exploratory and mastery behaviors are phylogenetically ancient tendencies that are subserved by dopaminergic systems. Studies also suggest that intrinsic motivation is associated with patterns of activity across large-scale neural networks, namely, those that support salience detection, attentional control, and self-referential cognition. We suggest novel research directions and offer recommendations for the application of neuroscience methods in the study of intrinsic motivation.